Capacity Constraints and Beliefs about Demand - Nick Vikander (Tinbergen Institute, 2011)
This paper examines how a firm can strategically choose its capacity to manipulate consumer beliefs about aggregate demand. It looks at a market with social effects where consumers want to do what is popular, to buy what they believe others want to buy. By imposing a capacity constraint and setting a price just low enough for it to bind, the firm can fool certain naive consumers into believing that demand is greater than it actually is. This will in turn increase the willingness to pay of all consumers through social effects. In equilibrium, the firm will impose a capacity constraint whenever demand is lower than expected, even when the number of naive consumers is arbitrarily small.
Keywords: D80; L00; 330; capacity constraints; bandwagon effects; naive consumers; bounded rationality